Selective fermentation of Lactobacillus delbrueckii ssp. Bulgaricus SRFM-1 derived exopolysaccharide by Lactobacillus and Streptococcus strains revealed prebiotic properties. (June 2020) - Tang, Weizhi; Han, Shuo; Zhou, Jianzhong; Xu, Qian; Dong, Mingsheng; Fan, Xia; Rui, Xin; Zhang, Qiuqin; Chen, Xiaohong; Jiang, Mei; Wu, Junjun; Li, Wei
Graphical abstract: Highlights: In vitro fermentation profiles of three purified r-EPS fractions are presented; Fermentations with ten Lactobacillus, Streptococcus and two E. coli strains were performed; r-EPS fractions stimulated the growth of the lactobacilli and the streptococci strains; Primary and individual structures influenced the μmax and cell density of these strains; r-EPS from L. delbrueckii ssp. bulgaricus SRFM-1 has prebiotic properties. Abstract: The prebiotic potential of exopolysaccharide (r-EPS) structures released from Lactobacillus delbrueckii ssp. bulgaricus SRFM-1 was assessed using in vitro fermentations. Fermentations with pure cultures of Lactobacillus (nine strains) and a Streptococcus strain as well as two food-borne pathogenic Escherichia coli were performed. Scanning electron microscopy and Congo red testing revealed that the three r-EPS fractions had different individual structures. All r-EPS fractions were found to stimulate the growth of the lactobacilli and the Streptococcus strain and inhibit the growth of the E. coli strains. Additionally, the primary structure including molecular weight, monosaccharide composition and glycosidic linkages and the individual structures of three r-EPS fractions were found to influence the μmax and cell density of these strains. The results strengthen previous studies on the r-EPS from L. delbrueckii ssp. bulgaricus SRFM-1 and provide additional validation of r-EPS as a potentially novel prebiotic for incorporation in functional foods.